Biochars Derived from Gasified Feedstocks Increase the Growth and Improve Nutrient Acquisition of Triticum aestivum (L.) Grown in Agricultural Alfisols - Kristin M. Trippe; Stephen M. Griffith; Gary M. Banowetz; Gerald W. Whitaker (Agriculture, 2015)
Biochars are produced by low-oxygen gasification or pyrolysis of organic waste products, and can be co-produced with energy, achieving waste diversion and delivering a soil amendment that can improve agricultural yields. Although many studies have reported the agronomic benefits of biochars produced from pyrolysis, few have interrogated the ability of gasified biochars to improve crop productivity. An earlier study described the ability of a biochar that was derived from gasified Kentucky bluegrass (KB) seed screenings to impact the chemistry of acidic agricultural soils. However, that study did not measure the effects of the biochar amendment on plant growth or on nutrient acquisition. To quantify these effects we conducted a greenhouse study that evaluated wheat grown in agricultural soils amended with either the KB-based biochar or a biochar derived from a blend of woody mixed-waste. Our studies indicated that biochar amended soils promoted the growth of wheat in these agricultural alfisols. Our elemental analysis indicated that an attenuation of metal toxicity was likely responsible for the increased plant growth. The results of our study are placed in the context of our previous studies that characterized KB-sourced biochar and its effects on soil chemistry.